Sensing the Vocal Age - Managing Voice Touchpoints on Alexa - Johanna Franziska Gollnhofer; Sophie Schüller (Marketing Review St.Gallen, 2018)
Creating strong customer experiences by actively managing touchpoints is an executive's top priority. The vocal age, manifested in the rise of AI-enabled voice assistants and platforms, offers new forms of touchpoints, so-called voice touchpoints. This paper conceptualizes voice touchpoints and develops managerial recommendations.
Keywords: 650